Advancements in Epilepsy Treatment: Challenges, Innovations, and Social Impacts on Patients - Akram, Muhammad; Aslam, Muhammad Tayyab; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
Epilepsy-related seizures can range greatly, from focal seizures that can impact certain brain areas to widespread tonic-clonic seizures. Although the exact origin of epilepsy is sometimes unknown, the underlying reasons are many and include genetic factors, brain damage, infections, stroke, tumors, and developmental abnormalities. The goal of both pharmaceutical and non-pharmacological treatments for epilepsy is to avoid seizures. With the aim of controlling seizures, antiepileptic medications (AEDs) are the first line of treatment for the majority of patients. However, about one-third of individuals with epilepsy suffer from drug-resistant seizures, which can cause cognitive, psychological, and social issues and have a significant impact on their quality of life. In these cases, alternative treatments like deep brain stimulation, vagus nerve stimulation, ketogenic diets, and surgery may be considered. New insights into the genetic and molecular mechanisms underlying epilepsy have created opportunities for personalized medicine, allowing for more focused therapeutic approaches. New treatment approaches have been made possible by the discovery of certain genetic mutations, changed ion channel function, and neuroinflammation in some forms of epilepsy. Even with these developments, there are still obstacles in the way of attaining ideal seizure control and raising epileptic patients' quality of life. Because individuals with epilepsy may experience stigmatization, discrimination, and obstacles to social integration, work, and education, the illness also has significant social ramifications. To improve outcomes for individuals with epilepsy, comprehensive care models, enhanced diagnostic technologies, and public awareness campaigns are essential. Additionally, the burden that epilepsy causes on people and society may be lessened with continued study into the neurobiological processes of seizures and the creation of more potent therapies.